Qualitative Approaches Towards Useful Photocatalytic Materials - Quesada-Cabrera, Raul; Parkin, Ivan P. (Frontiers in Chemistry, 2020)
The long-standing crusade searching for efficient photocatalytic materials have resulted in a vast landscape of promising candidates, as reflected by several new review papers in the last decade. Virtually all of these review papers focused on quantitative approaches aiming at understanding of the underlying mechanisms behind photocatalytic behaviour and the parameters that influence structure-function correlation. Less attention has been paid to a qualitative analysis around the development and assessment of photocatalysts towards the identification of a narrow range of promising materials. Such qualitative analysis is however crucial to ensure an efficient progression of photocatalysts from the discovery stage and into market applications. The current report provides a critical perspective over some of the main factors affecting the assessment of photocatalytic materials as a code of good practise, with several examples illustrating the most common pitfalls in the field. A case of study is also provided, where this qualitative analysis is applied to one of the most prolific materials of the last decade, a disorder-engineered, black titanium dioxide (TiO2).